The recent developments of the telephone - Lyman, Charles W. (My University, 1896)
Introduction: Electricity has been and is being put to innumerable uses, and one of its most important uses is in the transmission of sound. The mystery of its action is rather difficult to explain; but the mechanism by which it is produced is by no means obscure. Ever since 1831, when Wheat Stone found that vibrations set up in one place could be transmitted, through a medium, to another station, the “Telephone” has made a steady growth, although at times the growth was noticeable by outbreaks, until at present we are nearing perfection.
Citation: Lyman, Charles W. The recent developments of the telephone. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Electricity; Wheat stone; Telephone; Theses; Manuscripts (documents)